Changing treatment of hip fractures in Finland - Leino, Oskari K.; Forsbacka, Nora; Laaksonen, Inari E.; Mäkelä, Keijo T.; Matilainen, Markus; Ekman, Elina M. (Springer Nature, 2025)
Introduction: Hip fracture treatment should be as standardized and effective as possible, with emphasis on fast recovery and avoidance of complications, especially those leading to reoperations. There is accumulating evidence regarding the optimal treatment of hip fractures but reports of whether this has influenced treatment in the clinical setting are sparse. The objective of this study was to determine the trends of hip fracture incidence and treatment in Finland, with special regard to how we treat older patients compared to younger ones.
Materials and methods: All operatively treated hip fractures in Finland between 1997 and 2018 were identified from a national administrative register. The incidence of these fractures and operations performed to treat them were calculated based on the adult population size.
Results: Apart from a decline in the elderly age groups during the first half of the study period, the incidence of hip fractures remained relatively constant. However, the incidences of different operations changed significantly. In treatment of femoral neck fractures from 1997 to 2018, the incidence of cemented hemiarthroplasty (HA) increased from 41.1 to 59.9 per 100,000 person-years (105) and hybrid total hip arthroplasty (THA) from 0.56 to 5.93 per 105, while the incidence of internal fixation (IF) decreased, for instance screw fixation from 12.5 to 2.7 per 105. The incidence of cementless HA decreased from 13.3 to 1.2 per 105. These changes were much more pronounced in the elderly population and there was a statistically significant difference in the proportion of patients aged > 59 treated with cemented HA and IF in 1997 compared to 2018. For trochanteric and subtrochanteric fractures, treatment with intramedullary nails replaced extramedullary devices as the most common treatment method.
Conclusions: The changes in treatment methods in Finland correspond to the increasing knowledge available about the optimal treatment of hip fractures and global treatment trends.